2023
DOI: 10.3390/separations10030158
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Importance, Phytochemistry, Pharmacology, and Toxicological Attributes of the Promising Medicinal Herb Carissa spinarum L.

Abstract: Carissa spinarum L. (Apocynaceae), commonly known as Garna or Jungli Karonda, has a rich history of use in indigenous traditional medicinal systems owing to its tremendous medicinal and nutritional benefits. The present review aims to discuss the traditional uses, ethnopharmacology, bioactive composition, toxicity analysis, and biotechnological applications of Carissa spinarum L. (CS) to identify the gap between current applications and research conducted on this plant. We collected the literature published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Carissa spinarum was widely distributed throughout the collection site and has tremendous nutritional and medicinal potentials. The pharmacological studies by in vitro and in vivo experiments on C. spinarum discovered its anticonvulsant, anthelmintic, anti‐arthritic, antimicrobial, antidiabetic, anti‐inflammatory, hepatoprotective, antioxidant, vasorelaxant, antitumor, antihypertensive, wound‐healing, antipyretic effects, and anti‐venom properties (Sharma et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carissa spinarum was widely distributed throughout the collection site and has tremendous nutritional and medicinal potentials. The pharmacological studies by in vitro and in vivo experiments on C. spinarum discovered its anticonvulsant, anthelmintic, anti‐arthritic, antimicrobial, antidiabetic, anti‐inflammatory, hepatoprotective, antioxidant, vasorelaxant, antitumor, antihypertensive, wound‐healing, antipyretic effects, and anti‐venom properties (Sharma et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carissa spinarum kept much attention in the community as a magic tree (Slathia et al, 2017), attracting the users with its potential for treating several ailments. Carissa spinarum leaves are highly distributed with polyphenols (Sharma et al, 2023) and have traditionally been used for the treatment of diseases such as pneumonia (Ibrahim et al, 2010;Maobe et al, 2012). For instance, the analysis of phytochemicals in Carissa spinarum leaf extract was reported by Tiruneh et al (2022) to be trihydroxyl pentanoic acid, a polyphenol reported to contribute antibacterial activity against tested respiratory infectious pathogens (S. aureus, S. pneumoniae, and K. pneumoniae).…”
Section: List Of Figuresmentioning
confidence: 99%